Les publications japonaises sur la traduction : un aperçu - Gile, Daniel (Meta, 1988)
SummaryJapanese publications on translation are markedly more numerous than Western publications. They are aimed at the general public rather than at professionals or academics, and few are truly scientific or academic. They deal with the Japanese context, with hardly any reference to foreign publications, authors, ideas or translation activities. They are also short-lived and disappear from bookstores and publishers' stocks within a few years.Theoretical translation texts are "philosophical" rather than scientific. Didactic texts are often aimed at language learners rather than at would-be translators. Linguistic translation texts are more interesting for the insight they give into the Japanese language and its use than for their contribution to translation theory. Texts that criticize published translations are numerous and very popular, something which is rather unique in the world. Many translation books are highly personal and contain numerous anecdotes from their authors' lives. Interpretation books are interesting, as they are more pragmatic than Western texts on the same subject, and address questions that Western publications seldom or never refer to. Machine translation articles are becoming increasingly popular. They tend to be confined to superficial explanations of the operation of systems and to descriptions of commercial products. Truly scientific papers on MT also exist, but their circulation is limited to academic and technical circles.There are a few periodicals dealing with translation. Most of the articles they carry are written by the same authors and have the same characteristics as the texts described above. On the whole, they are more interesting than translation books, as they are shorter and therefore denser. Articles on translation can also be found in countless books and periodicals on the Japanese language, on linguistics, sociology, public speaking, etc., as well as in weekly and monthly magazines and in other publications.This paper is followed by a list of Japanese texts on translation and by a list of Western language texts on translation of Japanese or on subjects relevant to the understanding of Japanese translation problems.